Towards collaborative EU-Indonesia bargaining on palm oil policy : deconstructing the public discourse - Kettunen, Erja; Pratiwi, Ayu (Springer Nature, 2025)
Palm oil, one of the most contested commodities, has caused a trade dispute between  the EU and Indonesia due to its heavy impact on deforestation, biodiversity loss, and  social problems while providing a livelihood for millions of people. Discussing EU- Indonesia bargaining on palm oil policy, this paper investigates the positions of the  EU and Indonesia in the public discourse and aims to unpack the ‘good and bad’ narratives of palm oil. To do this, we explore international online news and examine  the perceptions, sentiments, and emotions reflected in the discourse. Both qualitative  and quantitative approaches are employed to (1) examine a narrative account of the  recent evolution of formal opinions between the EU and Indonesia and (2) perform  clustering, sentiment, and emotion analyses on the perceived positive and negative  facets, and positions of palm oil-related stakeholders in news articles published in  Indonesian and English language. The paper makes three main contributions. First, the findings indicate that the EU, despite its marginal role in Indonesia’s large palm  oil industry, has stronger bargaining power as exemplified in its deforestation regulation. Second, the debate in Indonesia is wrapped in perceptions of global trade and hints at new market opportunities in China and India, since the EU position is seen as a challenge to national autonomy. Third, the narrative has spurred not only uni-form but polarized sentiments amongst the Indonesian public, particularly on trade discrimination and the ensuing problems to smallholders. Indonesia, being the more vulnerable ‘norm taker’ in the bargaining with the EU, may increase exports to markets without sustainability standards, which would have adverse effects on global sustainability.